We Go on an Airplane - Mattern, Joanne, 1963- (Egremont, MA : Red Chair Press, 2020)
Simple text and photographs show how people go places on an airplane
Includes index
Keywords: Transportation -- Juvenile literature; Airplanes -- Juvenile literature